Pengembangan Pariwisata Berbasis Masyarakat di Taman Nasional Bromo Tengger Semeru Jawa Timur - Moh. Agus Sutiarso; Budi Susanto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
National Parks are regarded as having the best potential to provide for sustainable tourism development. National Parks management ideally brings together the concepts of conservation and that of recreational use with the objective of sustaining the natural environment.The specific objectives of this research are: 1) to study the development of tourism at Bromo Tengger Semeru National Park; 2) to study the contribution and the local people involvement in tourism activities. The largest number of the park visitors was Indonesia. Only 10% visitors were foreigners, of whom almost were European. Most of the visitors were aged 35 or under. The most common motivation for visiting the park (Mount Bromo) was to recreation and study. Tourism at Mount Bromo is rooted in the community, that the Tenggerese are benefitting from the industry through their individual involvement in tourism related enterprises (ownership of tourism services such as horse, jeep and home stay), and they are able to resist the incursion of outsiders and the over development. The ability to profit from private enterprise, coupled with a strong local identity. Tourism at Bromo Tengger Semeru National Park (Mount Bromo) can be directly and indirectly beneficial to people’s economic, social and cultural welfare. What is interesting about the case is that the local people (Tenggerese) has remained the principal beneficiary of the direct economic impacts by retaining firm control over ownership of tourism services, and this appears to be the key element in ensuring their prosperity.